2008
DOI: 10.1111/j.1095-8649.2007.01763.x
|View full text |Cite
|
Sign up to set email alerts
|

The stress and metabolic responses of juvenile Atlantic cod Gadus morhua L. to an acute thermal challenge

Abstract: Survival, oxygen consumption (M O2 ), total plasma cortisol and glucose levels and gill heat-shock protein 70 (hsp70) expression were measured in 10 and 50 g juvenile Atlantic cod Gadus morhua during an acute temperature increase (2°C h À1 ) to their critical thermal maximum. Ninety three per cent of the fish in both size classes survived to 24°C; however, mortality was 100% within 15 min of reaching this temperature. The M O2 for both size classes increased significantly with temperature, reaching peak values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
42
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 64 publications
(89 reference statements)
12
42
1
Order By: Relevance
“…The lowest Q 10 values of the snakehead were observed between 25 to 30°C, in consistent with its optimum temperature range for growth (25 to 30°C) (Liu et al, 1998). Our results also showed that the metabolic thermal sensitivity of the snakehead can be reduced by acclimation, represented by lower Q 10 value for RMR Accl than that for RMR Acute , which is consistent with previous results for the sandbar shark (Carcharhinus plumbeus), Atlantic cod (Gadus morhua), and southern catfish (Silurus meridionalis) (Dowd et al, 2006;Perez-Casanova et al, 2008;Zeng et al, 2011). It suggests a down-regulation in metabolism of this fish during acclimation for coping with the challenge due to the higher oxygen demand at higher temperature.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The lowest Q 10 values of the snakehead were observed between 25 to 30°C, in consistent with its optimum temperature range for growth (25 to 30°C) (Liu et al, 1998). Our results also showed that the metabolic thermal sensitivity of the snakehead can be reduced by acclimation, represented by lower Q 10 value for RMR Accl than that for RMR Acute , which is consistent with previous results for the sandbar shark (Carcharhinus plumbeus), Atlantic cod (Gadus morhua), and southern catfish (Silurus meridionalis) (Dowd et al, 2006;Perez-Casanova et al, 2008;Zeng et al, 2011). It suggests a down-regulation in metabolism of this fish during acclimation for coping with the challenge due to the higher oxygen demand at higher temperature.…”
Section: Discussionsupporting
confidence: 82%
“…Acute temperature change can cause a corresponding change in RMR of fish (Dowd, Brill, Bushnell, & Musick, 2006;PerezCasanova, Afonso, Johnson, & Gamperl, 2008). After long-term acclimation, many fish species show compensation for the direct effects of temperature change on metabolism, as reflected by recovery in RMR (Johnston & Dunn, 1987;Johnston, Guderley, Franklin, Crockford, & Kamunde, 1994;van Dijk, Tesch, Hardewig, & Pörtner, 1999;Aguiar, Kalinin, & Rantin, 2002;Ibarz, Fernández-Borràs, Blasco, Gallardo, & Sánchez, 2003;Perez-Casanova et al, 2008;Zhao, Dong, Wang, Tian, & Gao, 2011;Sandblom, Gräns, Axelsson, & Seth, 2014). The capacity of thermal compensation has been considered to be related with fitness and biogeographic range of ectothermal species under climate change (Chevin, Lande, & Mace, 2010;Somero, 2010;Schulte, Healy, & Fangue, 2011;Sandblom et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Glucose levels were found to increase both in response to higher packing density and increased length of confinement during this study, indicating an increased energy demand caused by stress. Similar increases in the blood/whole-body glucose level in response to various stressors such as, transportation, confinement, and handling have also been reported in other fish species (Specker and Schreck 1980;Iverson et al 1998;Pérez-Casanova et al 2008).…”
Section: Discussionsupporting
confidence: 55%
“…Both temperature differential (Brattey and Cadigan, 2004;Diamond and Campbell, 2009;Campbell et al, 2010) and high sea surface water temperature (Arlinghaus et al, 2007;Cooke and Wilde, 2007) have been shown to induce physiological disturbance and increase mortality in several species, including cod (Milliken et al, 2009;Weltersbach and Strehlow, 2013). However, maximum surface temperatures during the study (21.28C) never exceeded the thermal tolerance maximum of Atlantic cod (248C) and fell within the range that juvenile cod can tolerate during brief exposure (Pérez-Casanova et al, 2008), which could possibly explain the lack of negative effect on mortality. The lack of influence may also be attributable to the relatively small gradient in bottom vs. surface seawater differentials in the study area (see Table 5), or the short exposure period to warm surface water during capture and release.…”
mentioning
confidence: 80%